2012
DOI: 10.1111/and.12031
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Y chromosome microdeletions in childhood: lack of evidence for a direct association with testicular maldescent

Abstract: The aim of the study was to investigate the hypothesis that Y chromosome microdeletions are directly implicated in testicular maldescent. Genomic DNA was extracted from the peripheral blood of 292 subjects. This population consisted of (i) 180 children with all phenotypes of isolated (non-syndromic) testicular maldescent from 174 index families, (ii) affected adult relatives available (n = 12) and (iii) 100 unrelated children with normal external genitalia (controls). The sequence-tagged site primer set and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
1
2
0
1
Order By: Relevance
“…1,4,5 The role of several genetic factors, including Insulin-like 3 (INSL3) gene alterations, has recently been evaluated in a large study conducted at our institutions. [6][7][8] In line with other studies, it was concluded that known genetic factors are responsible for only a small proportion of TD impairment 3 and that novel candidate factors should be sought. [6][7][8] The aim of the present review is to summarize current knowledge on normal TD in the human, including evolutionary aspects and interspecies differences.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…1,4,5 The role of several genetic factors, including Insulin-like 3 (INSL3) gene alterations, has recently been evaluated in a large study conducted at our institutions. [6][7][8] In line with other studies, it was concluded that known genetic factors are responsible for only a small proportion of TD impairment 3 and that novel candidate factors should be sought. [6][7][8] The aim of the present review is to summarize current knowledge on normal TD in the human, including evolutionary aspects and interspecies differences.…”
Section: Introductionsupporting
confidence: 60%
“…91,134 The mechanism (direct or indirect) of androgenic action on the gubernaculum is controversial. It seems quite possible that androgens act indirectly 7 on the gubernaculum to mediate ISTD. AR localization studies in humans have demonstrated the presence of the receptor in the cremaster muscle but not in the gubernaculum.…”
Section: Istd Is Androgen-dependentmentioning
confidence: 99%
“…A total of 220 subjects derived from a previously described population (Mamoulakis et al ., , ) participated in the study. Patient population included 170 unrelated children with both testes present and at least one of them maldescended, exhibiting all phenotypes of nonsyndromic TMD.…”
Section: Methodsmentioning
confidence: 99%
“…Assim, outras linhas de investigação relacionadas a microdeleções do cromossomo Y passaram a ser desenvolvidas. Um exemplo disso é um estudo publicado em 2012 no qual o material genético de 180 meninos com criptorquidia foi analisado por meio da técnica de PCR Multiplex; nesse estudo não se encontrou associação entre microdeleções em Yq11 e falha na descida do testículo para a bolsa escrotal [60].…”
Section: Microdeleções No Cromossomo Yunclassified